A Digital Twin-Based Approach for Optimization and Prediction of Oil and Gas Production. (3rd September 2021) - Shen, Fei; Ren, Shuang Shuang; Zhang, Xiang Yang; Luo, Hong Wu; Feng, Chao Min
Abstract : The Internet of things technology plays an important role in improving the efficiency of oil and gas production, of which digital twin technology is the most prominent. By effectively using data and organically combining them with a deep understanding of technicians, digital twin technology can improve the efficiency of oil and gas asset systems in the entire life cycle of an oilfield including design, operation control, optimization, etc. Starting with the concept of digital twinning, this paper analyzes the situation of digital twinning in various industries, then obtains the new connotation of digital twinning in oil and gas industry, and at last establishes an optimization model of oil and gas production. Based on the digital twinning of oil and gas and applying the Internet of things, real-time data, and AI, the paper optimizes the oil and gas production process control and applies it to the actual production. Actually, the digital twin technology of oil and gas production includes six parts: entity, model, data collection, intelligent algorithm, service, and interaction control. Meanwhile, each part is interspersed with various data perception and drive, and interactive feedback forms an organic iterative closed-loop control. Digital twin technology can effectively use data and organically combine the deep understanding of technical personnel, so that it can be used in design, operation control, optimization, and other aspects including the entire life cycle of the oilfield from concept to front-end design and out-of-service . And digital twin technology would improve the efficiency of oil and gas asset systems. The example analysis shows that the system efficiency of the oil and gas production model based on digital twinning is improved by 3%. By analyzing the production status, optimizing the design, and fully grasping the production capacity, equipment capacity, and their working conditions of the oil layer, the digital twin-based approach can provide a basis for further formulating reasonable technical measures and make the equipment work normally at high efficiency to ensure high output and efficient production of oil wells.